Pengaruh Kekerasan Verbal Orangtua Terhadap Kepercayaan Diri Remaja Di Desa Girsang 1 Kecamatan Girsang Sipangan Bolon - Damanik, Anggita; Kurniawan, Fauzi (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2022)
The purpose of this study was to determine the influence of parental verbal violence on the self-confidence of adolescents aged 15-18 years in Girsang village 1, Girsang Sipangan Bolon District. The research method uses quantitative methods with a correlational approach. The population in this study was 85 with a sample of 37 people. Data analysis techniques use a tendency test, a simple linear test, a hypothesis test, a t-test and a determination test. Based on the results of data analysis, the level of inclination in variable X was obtained by 32.43%, which means that adolescents who received verbal violence from parents were in the moderate category, while in variable Y, a tendency level of 40.54% was obtained, which means that adolescent self-confidence is in the low category. The results of a simple linear regression obtained a value of Y = 3.017 + 0.702X which means that there is an influence between parental verbal violence on the self-confidence of adolescents aged 15-18 years in the village of Girsang. In the hypothesis test, the value of the correlation coefficient (rxy) of 0.784 using the t test obtained a calculation of > ttabel, namely 7.471 > 0.3246 which means that parental verbal violence (X) significantly affects the self-confidence of adolescents aged 15-18 years (Y). In the determination test, a score of 61.46% was obtained, which means that the influence of parental verbal violence on the self-confidence of adolescents aged 15-18 years in Girsang village was 61.46%, while the remaining 38.54% was influenced by other factors that were not included in this study.